Functional hemispherotomy in Rasmussen syndrome in the absence of classic MRI findings - Nagahama, Yasunori (Epilepsy Behav Case Rep, 2016)
A 7-year-old previously healthy girl presented with a left-sided focal seizure without impaired consciousness and subsequently developed epilepsia partialis continua. Initial MRI was normal, and the subsequent images only showed a focal T2/FLAIR hyperintense area without cortical atrophy. She was diagnosed with Rasmussen syndrome by pathology and promptly treated with functional hemispherotomy. Rasmussen syndrome is a rare progressive neurological disorder, the only definitive cure for which is hemispheric disconnection. The disease presents a management dilemma, especially early in disease course without characteristic neuroimaging features. A high index of suspicion, multidisciplinary approach, and clear timely communication with the family are critical.